Synopsis: Economywide assessment of CSA interventions in building resilient agri-food systems in Rwanda - Aragie, Emerta A.; Thurlow, James; Warner, James; Niyonsingiza, Josue (International Food Policy Research Institute, 2026)
This research extends IFPRI’s RIAPA modeling to include both the full implementation of PSTA 5’s climate smart agriculture and a once-in-five-year weather shock, and the interactions of both on agricultural sectors, agricultural GDP, and on national GDP. Main findings include: